300,000 quitters and counting; A systematic approach to tobacco cessation - Renee Fogelberg; Kelly C. Young-Wolff; Jaya Nadella; Mehreen Khan; Yi-Fen Irene Chen; Jamal S. Rana (American Journal of Preventive Cardiology, 2024)
Objective: To describe Kaiser Permanente Northern California's (KPNC) systematic implementation of universal tobacco screening, evidence-based interventions, and performance measures to achieve long-term smoking cessation success. Methods: We outline seven key components of KPNC's tobacco screening and intervention program that contributed to a significant decline in smoking prevalence. We also report changes in the prevalence of current smokers within KPNC from 2014 to 2023 using linear regression analyses. Results: Key factors driving the success of the tobacco cessation program included risk-based screening algorithms, alert prompts for at-risk patients, system-wide medical champions, performance tracking, virtual coaching, widespread messaging, and comprehensive medication management. Implementing this multifaceted approach across all facilities was associated with a significant reduction in smoking prevalence, from 8.6% in 2014 to 5.8% in 2023 (p < 0.0001). Conclusion: Our comprehensive, system-wide approach resulted in substantial public health gains and highlights the potential of similar preventive strategies as healthcare systems transition toward value-based care.